Antimicrobial potential of ozone: perspectives and uses in veterinary medicine - Nascente, Eduardo; Chagas, Sarah; Cândido Pessoa , Andréia; Matos, Moema; Andrade, Maria Auxiliadora; Pascoal , Livia (Pubvet, 2019)
When multidrug-resistant microorganisms emerged, the search for alternative methods that are able to destroy microorganisms and are environmentally sustainable has intensified. Ozone appears in this scenario for its high oxidative potential, being effective in inactivating and destroying bacteria, viruses, fungi, and even parasites. It is used as a disinfectant in many industries and in wastewater treatment. Recently, its applicability in veterinary medicine has been investigated. Experimental activities showed its high antibacterial potential in veterinary therapy, as a method for environmental disinfection in livestock and water treatment in fish farms. In summary, ozone contributes to increasing safety of food of animal origin.